Revision of the lichen genus Xanthoparmelia in Belarus: X. delisei and X. pulla - Tsurykau, Andrei G.; Halubkou, Uladzimir V.; Bely, Pavel M. (Experimental Biology and Biotechnology, 2019)
206 samples of genus Xanthoparmelia, collected on the territory of Belarus during 1905–2017 and housed in herbaria of Minsk (MSKL, MSKH, MSKU), Gomel (GSU), and Saint Petersburg (LE) were studied by means of thinlayer chromatography. Of these, 127 (61,7 %) specimens belong to Xanthoparmelia pulla group, and represent 4 species – X. delisei, X. loxodes, X. pulla, and X. verruculifera. X. delisei is reported for the first time to Belarus. X. pokornyi should be excluded from the lichen lists. Ecology and distribution of lichen species X. delisei and X. pulla are provided based on original data.